Does Precipitation and Runoff Variability Affect Treaty Cooperation between States Sharing International Bilateral Rivers? - Dinar, Ariel (2012)
Elevated world temperatures, as forecasted by the 4th IPCC report, are expected to increase the hydrological cycle activity, leading to a change in precipitation patterns and increase in evapotranspiration. These in turn are expected to affect river runoff and water variability, depending on basin latitude. In this paper, we assess the impact of water supply variability on 'treaty cooperation' (defined here as the likelihood of treaty formation and number of treaties formed) between international bilateral river basin riparian states. The water variability measure that we use captures both annual runoff variability and precipitation variability. We employ additional control variables adopted from economic and international relations theories on international cooperation. The main results suggest that water supply variability in international bilateral basins creates an impetus for cooperation. Our results support an inverted U-shaped relationship between water supply variability and treaty cooperation. Similarly, interactions between the states in the form of diplomatic and trade relations support cooperation. Various measures of democracy/governance suggest different impacts on cooperation. Uneven economic power between the riparian states inhibits treaty cooperation. The geography variables we use are insignificant in all the estimated relationships.